Graphene ink coated on diaphragm and graphene functionalized diaphragm

By coating graphene ink on the separator and performing heat treatment, the problem of poor conductivity of the separator coating in the prior art is solved, and the performance and life of the battery are significantly improved.

CN119401062APending Publication Date: 2025-02-07GUANGDONG TECHNION ISRAEL INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411467427.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the coating coated on the separator has poor electrical conductivity and cannot effectively improve battery performance.

Method used

Graphene ink composed of graphene nanosheets, polypropylene carbonate and organic solvents is prepared by ball milling and other methods, coated on the separator, and removed by heat treatment to form a loose structure to improve conductivity.

Benefits of technology

It significantly improves the conductive and electrochemical properties of the separator, extends the service life of the battery, and improves the rate performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401062A_ABST
    Figure CN119401062A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of diaphragms, in particular to graphene ink coated on a diaphragm and a graphene functionalized diaphragm. The invention provides graphene ink coated on a diaphragm. The graphene ink comprises graphene nanosheets, polypropylene carbonate and an organic solvent. According to the graphene ink which is formed by the graphene nanosheets, the polypropylene carbonate and the organic solvent and is coated on the diaphragm, the viscosity of the formed graphene ink is slightly influenced by temperature at a high shearing speed by utilizing the characteristic of high stability of the polypropylene carbonate, and the viscosity is reduced along with the increase of the shearing speed; the requirement of coating on a diaphragm can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diaphragms, and in particular to a graphene ink coated on a diaphragm and a graphene-functionalized diaphragm. Background Art

[0002] With the shortage of non-renewable resources, secondary batteries have experienced rapid development and become an indispensable energy storage technology in modern society. The sustainable development of rechargeable battery technology focuses on improving energy density and extending service life. However, the materials of rechargeable batteries usually have poor conductivity. Generally, the conductivity of rechargeable batteries is improved by adding conductive agents to the batteries. However, the addition of conductive agents will inevitably cause the proportion of active materials to be reduced, resulting in a decrease in the electrochemical performance of rechargeable batteries. In order to meet the improvement of conductivity and electrochemical performance, most active materials are currently coated on the surface of the current collector. In order to improve the energy density of the battery, a common method is to increase the load and proportion of active materials. However, using the traditional electrode coating method, the increase in active material load and the increase in electrode thickness will inevitably cause an increase in electrode resistance, which not only limits the performance of batteries with high active material loads, but also affects the service life of the battery. As an important component in a rechargeable battery, the diaphragm can achieve ion conduction and isolate the positive and negative electrodes to avoid safety hazards. Compared with the above-mentioned improvement method, coating the diaphragm with a coating can better solve the problems existing in rechargeable batteries.

[0003] The prior art discloses a composite diaphragm with adjustable coating, a preparation method thereof, and a lithium battery. Specifically, it is disclosed that a coating formed by organic components and inorganic components is applied to the sand-ground diaphragm to improve its electrochemical properties. However, the coating has poor viscosity when applied to the diaphragm and cannot improve its conductive properties. Therefore, it is still impossible to achieve a good improvement in battery performance. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor conductivity of the coating applied on the diaphragm in the prior art, thereby providing a graphene ink applied on the diaphragm.

[0005] Another technical problem to be solved by the present invention is to overcome the problem of poor conductivity of highly active material-loaded electrodes in the prior art, thereby providing a graphene-functionalized separator.

[0006] On the other hand, another technical problem to be solved by the present invention is to overcome the defect of poor electrochemical performance of rechargeable batteries in the prior art, thereby providing a graphene ink coated on a diaphragm and a graphene-functionalized diaphragm.

[0007] To this end, the present invention provides a graphene ink coated on a diaphragm, comprising graphene nanosheets, polypropylene carbonate and an organic solvent.

[0008] In some of the embodiments, the ratio of graphene nanosheets, polypropylene carbonate and organic solvent is (50-200):(3.5-300):1, and the unit is mg:mg:mL.

[0009] Preferably, the organic solvent is at least one of diethylene glycol ethyl ether, N-methyl-2-pyrrolidone or N,N-dimethylformamide.

[0010] The present invention also provides a method for preparing graphene ink coated on a diaphragm, comprising the following steps:

[0011] The graphene nanosheets containing polypropylene carbonate are mixed with an organic solvent to prepare graphene ink.

[0012] or,

[0013] The graphene nanosheets are mixed with a polypropylene carbonate solution to prepare graphene ink, wherein the polypropylene carbonate solution is a mixture of polypropylene carbonate and an organic solvent.

[0014] In some of the embodiments, the specific step of mixing the graphene nanosheets, polypropylene carbonate and the organic solvent is to mix the graphene nanosheets with the polypropylene carbonate solution under ball milling; or to mix the graphene nanosheets containing polypropylene carbonate with the organic solvent under ball milling.

[0015] Preferably, the ball milling speed is 500 rpm-2000 rpm, and the ball milling time is 30 min-6 h.

[0016] The concentration of polypropylene carbonate in the polypropylene carbonate solution is less than or equal to 300 mg / mL. Preferably, the concentration of polypropylene carbonate in the polypropylene carbonate solution is 300 mg / mL, 280 mg / mL, 250 mg / mL, 200 mg / mL, 170 mg / mL, 100 mg / mL, 60 mg / mL, 45 mg / mL, 20 mg / mL, 8 mg / mL, 3.5 mg / mL or an interval consisting of any two parameters.

[0017] Exemplarily, when the concentration of polypropylene carbonate in the polypropylene carbonate solution is 8 mg / mL (the solvent for preparing the polypropylene carbonate solution is diethylene glycol ethyl ether), the ratio of graphene nanosheets, polypropylene carbonate and organic solvent is 100:8:1, and the unit is mg:mg:mL, that is, take 100 mg of graphene nanosheets (the graphene nanosheets do not contain polypropylene carbonate) and 1 mL of polypropylene carbonate solution, mix them, and obtain graphene ink.

[0018] Exemplarily, when the concentration of polypropylene carbonate in the polypropylene carbonate solution is 100 mg / mL (the solvent for preparing the polypropylene carbonate solution is N-methyl-2-pyrrolidone), the ratio of graphene nanosheets, polypropylene carbonate and organic solvent is 100:50:1, and the unit is mg:mg:mL, that is, take 100 mg of graphene nanosheets (the graphene nanosheets do not contain polypropylene carbonate), 0.5 mL of organic solvent, and 0.5 mL of polypropylene carbonate solution, mix them, and obtain graphene ink.

[0019] Exemplarily, the ratio of graphene nanosheets, polypropylene carbonate and organic solvent is 100:8:1, and the unit is mg:mg:mL, that is, 100 mg of graphene nanosheets and 1 mL of organic solvent are mixed to obtain graphene ink, wherein the graphene nanosheets contain 8 wt% of polypropylene carbonate.

[0020] Exemplarily, when the concentration of polypropylene carbonate in the polypropylene carbonate solution is 100 mg / mL, the ratio of graphene nanosheets, polypropylene carbonate and organic solvent is 100:50:1, and the unit is mg:mg:mL, that is, 100 mg of graphene nanosheets, 0.6 mL of organic solvent, and 0.4 mL of polypropylene carbonate solution are taken and mixed to obtain graphene ink, wherein the graphene nanosheets contain 10 wt% of polypropylene carbonate.

[0021] Preferably, the organic solvent used in preparing the graphene ink is at least one of diethylene glycol ethyl ether, N-methyl-2-pyrrolidone or N,N-dimethylformamide.

[0022] Preferably, the organic solvent in the polypropylene carbonate solution is at least one of diethylene glycol ethyl ether, N-methyl-2-pyrrolidone or N,N-dimethylformamide.

[0023] In some of the embodiments, the method for preparing the graphene nanosheets containing polypropylene carbonate is to mix graphite and polypropylene carbonate in the presence of a solvent, separate the solid and the liquid to obtain an upper dispersion liquid as a graphene mixed liquid, separate the solid and the liquid of the obtained graphene mixed liquid to obtain a filter residue as graphene powder.

[0024] In some of the embodiments, during the preparation of the graphene nanosheets, the solvent is at least one of tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl acetate and diethylene glycol monomethyl ether.

[0025] Preferably, the mass ratio of the graphite to polypropylene carbonate is 1:(1-8).

[0026] In some of the embodiments, the method of mixing graphite and polypropylene carbonate comprises ultrasonically treating the graphite and polypropylene carbonate at 160W-360W for 2h-12h.

[0027] In some embodiments, the solid-liquid separation method comprises centrifuging the mixed graphite and polypropylene carbonate at a speed of 1000 rpm to 3000 rpm for 20 min to 60 min,

[0028] In some of the embodiments, the volume ratio of the sum of the mass of graphite and polypropylene carbonate to the solvent is (2-9):200, in units of mg:mL.

[0029] The present invention also provides a method for preparing a graphene-functionalized diaphragm, comprising the following steps: coating graphene ink on at least one surface of a diaphragm substrate, and obtaining the diaphragm after heat treatment, wherein the graphene ink is the above-mentioned graphene ink or a graphene ink prepared by the above-mentioned method for preparing the graphene ink.

[0030] In some embodiments, the coating process includes at least one of a printing process, a dipping process, and a spraying process.

[0031] In some embodiments, the heat treatment temperature is 150°C-250°C, and the heat treatment time is 30min-3h.

[0032] In some of the embodiments, before the heat treatment, a step of drying the membrane coated with the graphene ink is further included, and the drying temperature is 50° C.-120° C.

[0033] The present invention also provides a graphene-functionalized diaphragm prepared by the method for preparing the graphene-functionalized diaphragm, wherein the coating layer formed by the graphene has a thickness of 5 μm-100 μm.

[0034] The technical solution of the present invention has the following advantages:

[0035] 1. A graphene ink coated on a diaphragm provided by the present invention comprises graphene nanosheets, polypropylene carbonate and an organic solvent. The graphene ink coated on a diaphragm provided by the present invention comprises graphene nanosheets, polypropylene carbonate and an organic solvent. The graphene ink formed by the graphene nanosheets, polypropylene carbonate and an organic solvent utilizes the strong stability of polypropylene carbonate to form a graphene ink whose viscosity is less affected by temperature at high shear rates, and the viscosity decreases as the shear rate increases, which can meet the requirements for coating on the diaphragm.

[0036] 2. A method for preparing a graphene ink coated on a diaphragm provided by the present invention comprises the following steps: mixing a graphene nanosheet containing polypropylene carbonate with an organic solvent to obtain graphene ink, or mixing a graphene nanosheet with a polypropylene carbonate solution to obtain graphene ink, wherein the polypropylene carbonate solution is a mixture of polypropylene carbonate and an organic solvent. The present invention utilizes polypropylene carbonate mixed with graphene nanosheets and supplemented with an organic solvent, which not only increases the viscosity of the graphene ink, but also enhances the stability of the graphene ink.

[0037] 3. The present invention provides a method for preparing a graphene ink coated on a diaphragm, wherein the preparation method of the graphene nanosheets is to mix graphite and polypropylene carbonate in the presence of a solvent, separate the solid and liquid, obtain an upper mixed liquid as a graphene mixed liquid, separate the obtained graphene mixed liquid into solid and liquid, and obtain a filter residue as a graphene powder. The present invention uses polypropylene carbonate, an aliphatic thermoplastic plastic copolymerized by propylene oxide and carbon dioxide, as a dispersant, and utilizes the CH bond of polypropylene carbonate and the π bond of graphite to form a van der Waals bond, thereby increasing the liquid phase exfoliation yield of graphene, and the spatial repulsion between polypropylene carbonate molecules can enhance the dispersion stability of graphene, and the exfoliated graphene nanosheets have good stability. The graphene powder prepared by the present invention using graphite and polypropylene carbonate as raw materials contains 7-10wt% of polypropylene carbonate, and when the graphene nanosheets are applied to graphene ink, no additional polymer needs to be added.

[0038] 4. A method for preparing a graphene-functionalized diaphragm provided by the present invention comprises the following steps: coating the graphene ink on at least one surface of a diaphragm substrate, and obtaining the diaphragm after heat treatment. The method for preparing a graphene-functionalized diaphragm provided by the present invention has a simple process, and removes the polypropylene carbonate in the coating formed by the graphene ink on the diaphragm by heat treatment. After removing the polypropylene carbonate, the coating has an obvious loose structure, which increases the porosity of the coating and further improves the ionic and electronic conductivity of the coating.

[0039] 5. A method for preparing a graphene-functionalized diaphragm provided by the present invention, wherein the coating process includes at least one of a printing process, an impregnation process, and a spraying process. The diaphragm preparation process provided by the present invention can use a printing process to coat graphene ink on a diaphragm substrate. On the one hand, the present invention uses the above-mentioned graphene ink to adhere the graphene ink to the diaphragm surface through a printing process, and only through a printing process can the active material be loaded on the diaphragm surface, simplifying the coating steps; on the other hand, the present invention uses a printing process to coat the graphene ink on at least one surface of the diaphragm substrate, and the coating layer has high conductivity.

[0040] 6. The present invention provides a graphene-functionalized diaphragm, and proposes a method of increasing the electronic conduction path by coating the surface of the diaphragm with active substances to improve battery performance. The battery formed by the diaphragm has good rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is a result diagram of the polypropylene carbonate content in the graphene powder obtained by the TG thermogravimetric detection method in Preparation Example 1 of the present invention;

[0043] Figure 2 This is a physical picture of the diaphragm obtained in step (1) of Application Example 1 of the present invention;

[0044] Figure 3 is a SEM image of the diaphragm obtained in step (2) and step (3) of Application Example 1 of the present invention, wherein: Figure 3 a in the figure is the SEM image of the diaphragm obtained in step (2) of Application Example 1. Figure 3 b is the SEM image of the diaphragm obtained in step (3) of Application Example 1;

[0045] Figure 4 This is a graph showing the adhesion test results of graphene ink in Experimental Example 1 of the present invention;

[0046] Figure 5 1 is a graph showing the specific capacity test results of batteries formed by different separators at different charge and discharge rates in Experimental Example 2 of the present invention;

[0047] Figure 6 is a cycle performance diagram of batteries formed with different separators in Experimental Example 2 of the present invention;

[0048] Figure 7 1 is a graph showing the specific capacity test results of batteries formed by different separators at different charge and discharge rates in Experimental Example 3 of the present invention;

[0049] Figure 8 This is a graph showing the electrochemical impedance test results of the battery in Experimental Example 4 of the present invention. DETAILED DESCRIPTION

[0050] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0051] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0052] The structural formula of the polypropylene carbonate used in the preparation examples and embodiments of the present invention is shown in formula (I). The molecular weight of the polypropylene carbonate can be 500 kDa, 150 kDa, 50 kDa, 40 kDa, or 30 kDa. The polypropylene carbonate in the present invention was purchased from Sigma-Aldrich and has a molecular weight of 50 kDa.

[0053]

[0054] Preparation Example 1

[0055] This preparation example provides a method for preparing graphene, and the specific steps and parameters are as follows:

[0056] (1) dissolving 4 g of polypropylene carbonate in 200 mL of tetrahydrofuran solvent, adding 4 g of graphite powder thereto, subjecting the mixed solution to ultrasonic treatment at 200 W for 6 hours, and then centrifuging at 2000 rpm for 30 minutes, and taking out the upper mixed solution as the first graphene mixed solution;

[0057] (2) Filtering, drying, and grinding the first graphene mixed solution to obtain graphene powder.

[0058] See also Figure 1 Using the TG thermogravimetric measurement method, it was detected that the graphene powder prepared in this preparation example contained 8wt% of polypropylene carbonate.

[0059] Preparation Example 2

[0060] This preparation example provides a method for preparing graphene, and the specific steps and parameters are as follows:

[0061] (1) dissolving 16 g of polypropylene carbonate in 400 mL of ethyl acetate solvent, adding 2 g of graphite powder thereto, subjecting the mixed solution to ultrasonic treatment at 160 W for 12 hours, and then centrifuging at 1000 rpm for 60 minutes, and taking out the upper mixed solution as the first graphene mixed solution;

[0062] (2) Filtering, drying, and grinding the first graphene mixed solution to obtain graphene powder.

[0063] It was detected that the graphene powder prepared in this preparation example contained 9 wt % of polypropylene carbonate.

[0064] Preparation Example 3

[0065] This preparation example provides a method for preparing graphene, and the specific steps and parameters are as follows:

[0066] (1) dissolving 6 g of polypropylene carbonate in 800 mL of N-methyl-2-pyrrolidone solvent, adding 2 g of graphite powder thereto, ultrasonically treating the mixed solution at 360 W for 12 hours, and then centrifuging at 3000 rpm for 20 minutes, and taking out the upper mixed solution as the first graphene mixed solution;

[0067] (2) Filtering, drying, and grinding the first graphene mixed solution to obtain graphene powder.

[0068] It was detected that the graphene powder prepared in this preparation example contained 7 wt % of polypropylene carbonate.

[0069] Preparation Example 4

[0070] This preparation example provides a method for preparing graphene, and the specific steps and parameters are as follows:

[0071] (1) dissolving 4 g of polypropylene carbonate in 200 mL of diethylene glycol monomethyl ether solvent, adding 4 g of graphite powder thereto, ultrasonically treating the mixed solution at 300 W for 6 hours, and then centrifuging at 2000 rpm for 25 minutes, and taking out the upper mixed solution as the first graphene mixed solution;

[0072] (2) Filtering, drying, and grinding the first graphene mixed solution to obtain graphene powder.

[0073] It was detected that the graphene powder prepared in this preparation example contained 10 wt % of polypropylene carbonate.

[0074] Example 1

[0075] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are as follows:

[0076] (1) According to the ratio of graphene powder mass to solvent volume of 100:1, the unit is mg:mL, and the graphene powder prepared in Preparation Example 1 is mixed with diethylene glycol ethyl ether to obtain a mixed solution;

[0077] (2) The mixed solution was ball milled at a rotation speed of 2000 rpm for 1 hour to obtain a graphene ink coated on the diaphragm.

[0078] Example 2

[0079] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are as follows:

[0080] (1) polypropylene carbonate and diethylene glycol ethyl ether are mixed to obtain a polypropylene carbonate solution having a polypropylene carbonate concentration of 8 mg / L, and graphene powder, polypropylene carbonate and diethylene glycol ethyl ether are mixed in a ratio of 100:8:1 (in units of mg:mg:mL) to obtain a mixed solution, wherein the graphene powder is the graphene powder obtained in Preparation Example 1 after high-temperature treatment at 220°C to remove polypropylene carbonate, i.e., graphene powder not containing polypropylene carbonate;

[0081] (2) The mixed solution was ball milled at a rotation speed of 2000 rpm for 1 hour to obtain a graphene ink coated on the diaphragm.

[0082] Example 3

[0083] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are as follows:

[0084] (1) polypropylene carbonate and N,N-dimethylformamide are mixed to prepare a polypropylene carbonate solution having a polypropylene carbonate concentration of 8 mg / L, and graphene powder, polypropylene carbonate and diethylene glycol ethyl ether are mixed in a ratio of 100:8:1 (in units of mg:mg:mL) to obtain a mixed solution, wherein the graphene powder is commercial graphene nanosheets purchased on the market;

[0085] (2) The mixed solution was ball milled at a rotation speed of 2000 rpm for 1 hour to obtain a graphene ink coated on the diaphragm.

[0086] Example 4

[0087] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are as follows:

[0088] (1) polypropylene carbonate and N-methyl-2-pyrrolidone are mixed to obtain a polypropylene carbonate solution having a polypropylene carbonate concentration of 292 mg / L, and the graphene powder obtained in Preparation Example 1 and the polypropylene carbonate solution are mixed with diethylene glycol ethyl ether in a ratio of 200:292:1 of graphene powder, polypropylene carbonate and solvent (unit: mg:mg:mL) to obtain a mixed solution, wherein the graphene powder is commercial graphene nanosheets purchased on the market;

[0089] (2) The mixed solution was ball-milled at a rotation speed of 2000 rpm for 30 minutes to obtain a graphene ink coated on the diaphragm.

[0090] Example 5

[0091] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are as follows:

[0092] (1) According to the ratio of graphene powder mass to solvent volume of 100:1, the unit is mg:mL, and the graphene powder prepared in Preparation Example 1 is mixed with diethylene glycol ethyl ether to obtain a mixed solution;

[0093] (2) The mixed solution was ball-milled at a rotation speed of 500 rpm for 6 hours to obtain a graphene ink coated on the diaphragm.

[0094] Example 6

[0095] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are the same as those in Example 1, except that an equal volume of N-methyl-2-pyrrolidone is used to replace diethylene glycol ethyl ether in step (1).

[0096] Example 7

[0097] This embodiment provides a method for preparing a graphene ink coated on a diaphragm, wherein the specific steps and parameters are the same as those in Embodiment 1, except that an equal volume of N,N-dimethylformamide is used to replace diethylene glycol ethyl ether in step (1).

[0098] Comparative Example

[0099] This comparative example provides a method for preparing a graphene ink coated on a diaphragm, and the specific steps and parameters are the same as those in Example 2, except that an equal mass of polyvinyl pyrrolidone (PVP) is used to replace the polypropylene carbonate in step (1).

[0100] Application Example 1

[0101] This application example provides a method for preparing a diaphragm, and the specific steps and parameters are as follows:

[0102] (1) Using a glass fiber diaphragm as a base material, a printed pattern template is covered on the base material, and the graphene ink prepared in Example 1 is filled into the pattern template by scraping to obtain a diaphragm printed with graphene. The actual diaphragm is shown in FIG. Figure 2 ;

[0103] (2) Remove the template and dry the membrane at 80°C to remove the solvent in the ink. The SEM image of the graphene coating on the membrane after the solvent is removed is shown in Figure 3 a in;

[0104] (3) After the solvent is removed, the diaphragm is heat treated in a high temperature furnace at 220°C for 2 h to remove the polypropylene carbonate in the graphene ink. The SEM image of the graphene coating of the diaphragm without polypropylene carbonate is shown in Figure 3 From b in the figure, it can be seen that after removing polypropylene carbonate, the graphene layer coated on the surface of the diaphragm has a loose structure and the porosity is improved.

[0105] The thickness of the coating on the diaphragm prepared in this application example is 30 μm.

[0106] Application Example 2

[0107] This application example provides a method for preparing a diaphragm. The specific steps and parameters are the same as those of Application Example 1, except that the graphene ink prepared in Example 2 is used to replace the graphene ink in step (1) of Application Example 1.

[0108] Application Example 3

[0109] This application example provides a method for preparing a diaphragm, and the specific steps and parameters are as follows:

[0110] (1) Using a cellulose diaphragm and a glass fiber diaphragm as a base material, a printed pattern template is covered on the base material, and the graphene ink prepared in Example 1 is filled into the pattern template by a doctor blade coating method to obtain a diaphragm printed with graphene;

[0111] (2) Remove the template, dry the membrane at 120° C. to remove the solvent in the ink, and then heat treat the membrane at 150° C. for 3 h to remove the solvent and polypropylene carbonate in the ink;

[0112] The thickness of the coating on the diaphragm prepared in this application example is 100 μm.

[0113] Application Example 4

[0114] This application example provides a method for preparing a diaphragm. The specific steps and parameters are the same as those of Application Example 1, except that the graphene ink prepared in Comparative Example 1 is used to replace the graphene ink in step (1) of Application Example 1.

[0115] However, since the thermal decomposition temperature of PVP is about 350°C, a decomposition rate of more than 90% can be achieved at 500°C. This results in the quality of the diaphragm being affected if the temperature is too high when removing the polymer in the graphene ink printed on the diaphragm during high-temperature treatment. If the temperature is too low, polymer residues will be left, affecting the conductivity and ion migration ability of the diaphragm printed with graphene ink, and reducing the electrochemical performance and stability of the battery.

[0116] Application Example 5

[0117] This application example provides a method for preparing a diaphragm. The specific steps and parameters are the same as those of Application Example 1. The difference is that the thickness of the coating on the diaphragm prepared in this application example is 5 μm.

[0118] Experimental Example 1

[0119] The viscosity of the graphene ink prepared in Example 1 at different speeds was measured using a rheometer at 15°C, 25°C and 35°C, respectively. Figure 4 .

[0120] Results Figure 4 It can be seen that the graphene ink prepared in the embodiment of the present invention is -1 ), and the viscosity is less affected by temperature, and the viscosity decreases with increasing shear rate, which proves that the graphene ink provided by the present invention is suitable for use as printing ink, and can be well adhered to the diaphragm by printing, simplifying the coating step.

[0121] Experimental Example 2

[0122] The button cells were assembled in an argon-protected glove box for electrochemical performance testing. The main structure of the button cell includes lithium iron phosphate positive electrode sheets with different active material loadings, diaphragms, and lithium sheets. The preparation method of the lithium iron phosphate electrode sheet is as follows: the slurry is applied on aluminum foil by coating to form a positive electrode sheet with an active material loading of 15 mg / cm 2 The mass ratio of lithium iron phosphate active material, conductive carbon black and polytetrafluoroethylene binder in the slurry is 90:5:5; the solvent is NMP;

[0123] The diaphragm printed with graphene ink prepared in step (3) of Application Example 1 and the glass fiber diaphragm as the base material provided in step (1) of Application Example 1 are respectively assembled into button batteries, wherein the diaphragm printed with graphene ink prepared in step (3) of Application Example 1 contacts the lithium iron phosphate positive electrode plate with the side printed with ink, and the assembled battery is subjected to a constant rate charge and discharge performance test, the battery charge and discharge voltage range is 2.5V-4V, the nominal capacity of lithium iron phosphate is 1C at 170mAh / g, the battery formed by the diaphragm printed with graphene ink prepared in step (3) of Application Example 1 is the experimental group, and the battery formed by the glass fiber diaphragm as the base material provided in step (1) of Application Example 1 is the control group.

[0124] The specific capacities of the batteries in the experimental group and the control group were measured at different charge and discharge rates. The charge and discharge rates were 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 0.1C, respectively. Each charge and discharge rate was repeated for 5 cycles.

[0125] Results Figure 5It can be seen that compared with the glass fiber diaphragm, the battery formed by the diaphragm printed with graphene ink prepared in Application Example 1 of the present invention has excellent specific capacity performance at a charge and discharge rate of 0.1-5C.

[0126] The cycle capacity retention rate of the batteries in the experimental group and the control group at a rate of 0.5C was measured. The results are shown in Figure 6 It can be seen that compared with the battery formed by the glass fiber diaphragm, the capacity retention rate decays to 35% after 100 cycles. The battery formed by the diaphragm printed with graphene ink prepared in Application Example 1 of the present invention has a capacity retention rate of 93% after 200 cycles at a rate of 0.5C, which proves that the battery formed by the diaphragm printed with graphene ink can improve the battery's cycle performance and extend the battery's service life.

[0127] Experimental Example 3

[0128] The steps and parameters are the same as those in Experiment 2, except that the preparation method of the lithium iron phosphate electrode is as follows: the slurry is applied on aluminum foil by coating to form an active material loading of 20 mg / cm 2 The mass ratio of lithium iron phosphate active material, conductive carbon black and polytetrafluoroethylene binder in the slurry is 95:3:2; the solvent is NMP.

[0129] Among them, the battery formed by the diaphragm printed with graphene ink prepared in Application Example 1 is the experimental group, and the battery formed by the base material glass fiber diaphragm provided in step (1) of Application Example 1 is the control group.

[0130] Results Figure 7 It can be seen that the battery formed by the diaphragm printed with graphene ink provided by the present invention has good specific capacity performance and relatively stable performance under high active material loading and low proportion of conductive additives.

[0131] Experimental Example 4

[0132] The electrochemical impedance test was performed using the batteries of the experimental group and the control group in Experimental Example 2, with a test frequency range of 1MHz-10mHz. The results are shown in Figure 8 The highly conductive printed graphene coating of the present invention can significantly reduce the internal resistance of the battery, thereby improving the rate performance and cycle life of the high-load electrode.

[0133] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A graphene ink coated on a diaphragm, characterized in that: The invention comprises graphene nanosheets, polypropylene carbonate and an organic solvent.

2. The graphene ink according to claim 1, characterized in that: The ratio of graphene nanosheets, polypropylene carbonate and organic solvent is (50-200):(3.5-300):1, in units of mg:mg:mL; and / or, The organic solvent is at least one of diethylene glycol ethyl ether, N-methyl-2-pyrrolidone or N,N-dimethylformamide.

3. A method for preparing the graphene ink coated on a diaphragm according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: mixing graphene nanosheets containing polypropylene carbonate with an organic solvent to prepare graphene ink; or, The graphene nanosheets are mixed with a polypropylene carbonate solution to prepare graphene ink, wherein the polypropylene carbonate solution is a mixture of polypropylene carbonate and an organic solvent.

4. The method for preparing graphene ink according to claim 3, characterized in that: The specific steps of mixing the graphene nanosheets containing polypropylene carbonate with an organic solvent, or mixing the graphene nanosheets with a polypropylene carbonate solution are: The raw materials are mixed by ball milling, the speed of the ball milling is 500 rpm-2000 rpm, and the ball milling time is 30 min-6 h; and / or, When the graphene nanosheets containing polypropylene carbonate are mixed with an organic solvent, the step of adding a polypropylene carbonate solution thereto is also included; and / or, When the graphene nanosheets are mixed with the polypropylene carbonate solution, the method further comprises the step of adding an organic solvent thereto.

5. The method for preparing graphene ink according to claim 3, characterized in that: The concentration of polypropylene carbonate in the polypropylene carbonate solution is less than or equal to 300 mg / mL; and / or, The organic solvent is at least one of diethylene glycol ethyl ether, N-methyl-2-pyrrolidone or N,N-dimethylformamide; and / or, The preparation method of the graphene nanosheet containing polypropylene carbonate comprises the following steps: mixing graphite and polypropylene carbonate in the presence of a solvent, performing solid-liquid separation, obtaining an upper dispersion liquid as a graphene mixed liquid, performing solid-liquid separation on the obtained graphene mixed liquid, and obtaining a filter residue as graphene powder.

6. The method for preparing graphene ink according to claim 5, characterized in that: In the preparation process of the graphene nanosheets, the solvent is at least one of tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl acetate and diethylene glycol monomethyl ether. The mass ratio of graphite to polypropylene carbonate is 1:(1-8), The method for mixing graphite and polypropylene carbonate comprises subjecting the graphite and polypropylene carbonate to ultrasonic treatment at 160W-360W for 2h-12h, The solid-liquid separation method comprises centrifuging the mixed graphite and polypropylene carbonate at a speed of 1000 rpm to 3000 rpm for 20 min to 60 min, The volume ratio of the total mass of graphite and polypropylene carbonate to the solvent is (2-9):200, in units of mg:mL.

7. A method for preparing a graphene-functionalized diaphragm, characterized in that: The method comprises the following steps: coating graphene ink on at least one surface of a diaphragm substrate, and obtaining a diaphragm after heat treatment. The graphene ink is the graphene ink described in any one of claims 1-2 or the graphene ink prepared by the preparation method of the graphene ink described in any one of claims 3-6.

8. The method for preparing a diaphragm according to claim 7, characterized in that: The coating process includes at least one of a printing process, a dipping process, and a spraying process; and / or, The heat treatment temperature is 150°C-250°C, and the heat treatment time is 30min-3h; and / or, Before the heat treatment, the method further includes a step of drying the diaphragm coated with the graphene ink, wherein the drying temperature is 50° C.-120° C.

9. A graphene-functionalized diaphragm, characterized in that: The graphene-functionalized diaphragm is prepared by the diaphragm preparation method according to any one of claims 7 to 8.

10. The graphene-functionalized diaphragm according to claim 9, characterized in that: The coating layer formed by graphene has a thickness of 5 μm-100 μm.